Effect of Acute Coronary Syndrome Probability on Diagnostic and Prognostic Performance of High-Sensitivity Cardiac Troponin. (1st March 2018) - Badertscher, Patrick; Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; Wildi, Karin; Sabti, Zaid; Puelacher, Christian; Rubini Giménez, Maria; Pfäffli, Julian; Flores, Dayana; du Fay de Lavallaz, Jeanne; Miró, Òscar; et al.
Abstract: BACKGROUND: There is concern that high-sensitivity cardiac troponin (hs-cTn) may have low diagnostic accuracy in patients with low acute coronary syndrome (ACS) probability. METHODS: We prospectively stratified patients presenting with acute chest discomfort to the emergency department (ED) into 3 groups according to their probability for ACS as assessed by the treating ED physician using a visual analog scale: ≤10%, 11% to 79%, and ≥80%, reviewing all information available at 90 min. hs-cTnT and hs-cTnI concentrations were determined in a blinded fashion. Two independent cardiologists adjudicated the final diagnosis. RESULTS: Among 3828 patients eligible for analysis, 1189 patients had low (≤10%) probability for ACS. The incidence of non-ST-segment elevation myocardial infarction (NSTEMI) increased from 1.3% to 12.2% and 54.8% in patients with low, intermediate, and high ACS probability, respectively. The positive predictive value of hs-cTnT and hs-cTnI was low in patients with low ACS probability and increased with the incidence of NSTEMI, whereas the diagnostic accuracy of hs-cTnT and hs-cTnI for NSTEMI as quantified by the area under the curve (AUC) was very high and comparable among all 3 strata, e.g., AUC hs-cTnI, 0.96 (95% CI, 0.94–0.97); 0.87 (95% CI, 0.85–0.89); and 0.89 (95% CI, 0.87–0.92), respectively. Findings were validated using bootstrap analysis as an alternative methodology to define ACS probability. Similarly, higher hs-cTnT/I concentrations independently predicted all-cause mortality within 2 years (e.g., hs-cTnT hazard ratio, 1.39; 95% CI, 1.27–1.52), irrespective of ACS probability. CONCLUSIONS: Diagnostic and prognostic accuracy and utility of hs-cTnT and hs-cTnI remain high in patients with acute chest discomfort and low ACS probability. ClinicalTrials.gov Identifier: NCT00470587.